An ethical defense of cryptocurrencies. Issue 3 (8th May 2021) - Bagus, Philipp; de la Horra, Luis P.
Abstract: The growing importance of the cryptocurrency phenomenon has raised concerns about the ethical implications of a hypothetical widespread use of these new forms of digital money. In this paper, we undertake an ethical assessment of cryptocurrencies drawing upon two specific ethical theories: private property ethics and utilitarianism. Particularly, we focus on three distinctive aspects. First, we examine the advantages and disadvantages of cryptocurrencies vis‐à‐vis central bank fiat money. Second, we analyze cryptocurrencies as facilitators of tax evasion and the ethical implications arising therefrom. Finally, we explore the use of cryptocurrencies for nefarious consumption. We conclude that, were cryptocurrencies to become widespread media of exchange, governments capacity to undertake monetary, fiscal, and drug policy would be undermined. We argue that this would be an ethically desirable outcome from both a private‐property‐rights and a utilitarian perspective since it would force governments to reduce their size and scope in these three areas.